TEORI BELAJAR HUMANISTIK DAN IMPLEMENTASINYA DALAM PELAJARAN PENDIDIKAN AGAMA ISLAM - Erna Nur Utami (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Many students currently do not understand the meaning of the purpose of their learning process. In the end they are only competing to pursue the best value regardless of how to implement the surrounding environment. Humanistic theory is basically the concept of learning that provides an explanation of how to humanize students and actualize all the potential abilities of each student to deal with changes in the environment around him. This theory assumes learning will not be meaningful if there is coercion in it. This paper aims to further examine the humanistic theory and its implementation in Islamic Religious Education lessons. This humanistic learning theory can be used by an educator on how to deliver Islamic Religious Education material. Helping educators better know how to humanize students either through material or linking material with real experiences. The application of humanistic learning theory in Islamic Religious Education lessons using creative, active, and fun learning strategies.